Lmx1a is required for the development of the ovarian stem cell niche in Drosophila. - Allbee, A.W.; Rincon-Limas, D.E.; Biteau, B. (Development, 2018)
The Drosophila ovary serves as a model for pioneering studies of stem cell niches, with defined cell types and signaling pathways supporting both germline and somatic stem cells. The establishment of the niche units begins during larval stages with the formation of terminal filament-cap structures; however, the genetics underlying their development remains largely unknown. Here, we show that the transcription factor Lmx1a is required for ovary morphogenesis. We found that Lmx1a is expressed in early ovarian somatic lineages and becomes progressively restricted to terminal filaments and cap cells. We show that Lmx1a is required for the formation of terminal filaments, during the larval-pupal transition. Finally, our data demonstrate that Lmx1a functions genetically downstream of Bric-à-Brac, and is crucial for the expression of key components of several conserved pathways essential to ovarian stem cell niche development. Importantly, expression of chicken Lmx1b is sufficient to rescue the null Lmx1a phenotype, indicating functional conservation across the animal kingdom. These results significantly expand our understanding of the mechanisms controlling stem cell niche development in the fly ovary.